PENGARUH PRODUK DOMESTIK BRUTO, SALES GROWTH, DAN INVENTORY TURNOVER TERHADAP RETURN ON ASSETS PADA PERUSAHAAN CONSUMER GOODS YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2019-2021 - Anak Agung Mayun Eka Dharma; Ni Nyoman Sri Rahayu Trisna Dewi; Laras Oktaviani (Universitas Triatma Mulya, 2023)
The purpose of this study is to examine the effect of GDP, sales growth and inventory turnover on ROA. This research is a quantitative research. The population in this study were 45 companies and the sample technique used in this study was purposive sampling in order to obtain a total sample of 54 samples. The data analysis technique used is multiple linear regression analysis. The results of the analysis show that, (1) GDP has an effect on ROA in consumer goods companies listed on the Indonesia Stock Exchange, (2) sales growth has an effect on ROA on consumer goods companies listed on the Indonesia Stock Exchange, (3) inventory turnover has an effect on ROA in consumer goods companies listed on the Indonesia Stock Exchange.